Solvothermally synthesized anatase TiO2 nanoparticles for photoanodes in dye-sensitized solar cells - Attafi, Kadhim (Sci Technol Adv Mater, 2021)
Many researchers working on the development of Dye-sensitized solar cells (DSCs) continue to focus on the synthesis of photoanode materials with high surface area, along with high light scattering ability to enhance light harvesting efficiency (LHE). On the other hand, dye packing density, which can also affect the LHE significantly, is often overlooked. Solvothermally synthesized anatase TiO(2) nanoparticles (SANP) were obtained by a new and simple approach using a mixed solvent, ethanol and acetic acid. SANP were applied as a photoanodes material in DSCs using a metal-free organic dye (D149) or organometallic dye (N719) dyes. The dye loading (packing density) was examined in term of the isoelectric point (IEP) and the contribution of this, in addition to light scattering effects were shown to control the devices photovoltaic efficiency of the devices; specifically when compared with ones employing commercially available TiO(2) nanoparticles (either transparent or a bilayer structure with a transparent layer and a scattering one). SANP photoanodes sensitized with D149 dye were found to be optimised at 10 µm, yielding photovoltaic conversion efficiencies of 6.9%, superior to for transparent or transparent + scattering films from the commercial source (5.6% and 5.9%, respectively). Further to this, an efficiency of 7.7% PCE was achieved using a SANP photoanode sensitized with N719 dye, with 7.2% seen for the transparent photoanode and 7.9% with a scattering layer. The high efficiencies of devices based on of SANP photoanode are attributed to the high dye loading capability in addition to good light scattering. A further point of interest is that even with the increased reactivity of the surface towards dye adsorption, we did not observe any significant increase in recombination with the redox mediator, presumably due to this increased dye loading providing better shielding.